Application of adoptive cell therapy in malignant melanoma - Qianrong Hu; Jiangying Xuan; Lu Wang; Kangjie Shen; Zixu Gao; Yuhong Zhou; Chuanyuan Wei; Jianying Gu (Journal of Translational Medicine)
Abstract Cutaneous melanoma is one of the most aggressive skin cancers originating from skin pigment cells. Patients with advanced melanoma suffer a poor prognosis and generally cannot benefit well from surgical resection and chemo/target therapy due to metastasis and drug resistance. Thus, adoptive cell therapy (ACT), employing immune cells with specific tumor-recognizing receptors, has emerged as a promising therapeutic approach to display on-tumor toxicity. This review discusses the application, efficacy, limitations, as well as future prospects of four commonly utilized approaches -including tumor-infiltrating lymphocytes, chimeric antigen receptor (CAR) T cell, engineered T-cell receptor T cells, and chimeric antigen receptor NK cells- in the context of malignant melanoma.